A neuroprotective phase precedes striatal degeneration upon nucleolar stress - Kreiner, Grzegorz; Bierhoff, Holger; Armentano, M.; Rodriguez-Parkitna, Jan; Sowodniok, Katharina; Naranjo, J. R.; Bonfanti, L.; Liss, B.; Schütz, Günther; Grummt, Ingrid; Parlato, Rosanna (Cell death and differentiation, 2013)
The nucleolus is implicated in sensing and responding to cellular stress by stabilizing p53. The pro-apoptotic effect of p53 is associated with several neurodegenerative disorders, including Huntington’s disease (HD), which is characterized by the progressive loss of medium spiny neurons (MSNs) in the striatum. Here we show that disruption of nucleolar integrity and function causes nucleolar stress and is an early event in MSNs of R6/2 mice, a transgenic model of HD. Targeted perturbation of nucleolar function in MSNs by conditional knockout of the RNA polymerase I-specific transcription initiation factor IA (TIF-IA) leads to late progressive striatal degeneration, HD-like motor abnormalities and molecular signatures. Significantly, p53 prolongs neuronal survival in TIF-IA-deficient MSNs by transient upregulation of phosphatase and tensin homolog deleted on chromosome 10 (PTEN), a tumor suppressor that inhibits mammalian target of rapamycin signaling and induces autophagy. The results emphasize the initial role of nucleolar stress in neurodegeneration and uncover a p53/PTEN-dependent neuroprotective response.
Gesehen am 27.10.2021